Comparison of behavioral activation/inhibition systems, emotional regulation difficulties, and selective attention in adolescents with and without parents - Sadeghzadeh, Zohreh; Bagheri, Fariborz (Frontiers in Psychology, 2023)
Existing literature has established a relationship between adverse childhood experiences and negative outcomes in cognitive and affective functioning. However, further research is needed to thoroughly understand and validate these findings. In this regard, the current study aimed to compare behavioral activation/inhibition systems, emotional regulation difficulties, and selective attention in adolescents with and without parents. A sample of 70 adolescents (M age = 16.36, SD = 1.09, 48.57% female) with caretakers from schools and 55 parentless adolescents (M age = 16.58, SD = 1.28, 52.00% female) from orphanage centers in Tehran were recruited and completed the measures tapping behavioral activation/inhibition systems, emotion dysregulation difficulties, and selective attention. The results revealed that parentless adolescents exhibited significantly higher levels of behavioral activation/inhibition scores, emotion regulation difficulties, and impaired selective attention. These findings suggest that the absence of parents during the early years of life may have detrimental effects on behavioral inhibition and activation systems, emotional regulation abilities, and selective attention capabilities. The implications of these findings are further discussed.